The impact of regional factors and new bio-methane incentive schemes on the structure, profitability and CO2 balance of biogas plants in Italy. (December 2016) - Patrizio, P.; Chinese, D.
Abstract: The Italian Ministry for Economic Development recently started a new incentive program for biomethane grid injection and biomethane for transportation. This opens up new opportunities for more efficient utilization of agricultural biogas, which in the past was mainly used in Italy for power only solutions. Because of the wider range of feasible options, entrepreneurs and local authorities need support tools to identify optimal alternatives, from an economic and environmental viewpoint, respectively. Thus, a biomass supply chain optimization model, including current costs and new incentives for biogas exploitation, is introduced in this paper. The model is used to explore the impact of Italian energy policies on the profitability of alternative biogas utilization pathways in two regional cases studies, characterized by different penetration of CNG refueling stations. The effect of local factors on energy vectors share and on GHG emission reduction are investigated with factor analysis. It is found that CBM production represents the most profitable choice for entrepreneurs under current levels of bio-methane incentives, however because of the small Italian CBM market size it risks to be overly subsidized. Allocating funds to promote a further expansion of CNG would probably help CBM development and benefits more than increasing specific incentives. Highlights: The impact of Italian energy policies on the profitability of biogas utilization pathways have been investigated. Previous and current Italian biogas promotion schemes have been included in the optimization process. The effect of local factors on the economic and environmental performance of the biogas supply chain have been investigated. Results show that CBM option gives the highest profits, but specific investments in refueling infrastructure are required.